SENI SYAIR GULUNG SEBAGAI SARANA EDUKASI MORAL PADA MASYARAKAT DI KABUPATEN KETAPANG - Hasmidar, Oktaviani; Noor, Agus Sastrawan; Firmansyah, Andang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to find out and describe about 1) The history of syair gulung in Ketapang Regency, 2) What values are contained in syair gulung, 3) The role of the community in applying the values contained in the syair gulung. The research method used is qualitative descriptive document analysis. Data sources used are informants and documents. Data collection techniques using direct observation, interviews and documents. While data validation uses data analysis and triangulation techniques. Based on the results of the study it can be concluded that the art of syair gulung is one of the Malay cultural arts of Ketapang Regency which is still preserved today because in the contents of the syair gulung contains moral education values such as moral education of humans with humans, humans with themselves, humans with nature and humans with His god. Syair gulung plays an important role in social life because the values in syair gulung are adaptations of the norms and customs of the community itself. therefore syair gulung exists in every event and gathering in the community as a medium to convey moral messages.Keywords: Syair Gulung, Moral Education